1994
DOI: 10.1111/j.1469-7998.1994.tb08586.x
|View full text |Cite
|
Sign up to set email alerts
|

Interclutch and interpopulation variation in the effects of incubation conditions on sex, survival and growth of hatchling turtles (Chelydra serpentina)

Abstract: With 5 figures in the text)We tested the hypothesis that larger egg and hatchling sizes in the snapping turtle confer posthatching advantages, by comparing the growth rates and survival of hatchlings from different thermal and hydric environments during embryonic development. We also tested for sex-specific differences in survival and growth, two indices of hatchling fitness, as predicted by the Charnov & Bull (1977) model of environmental sex determination (ESD). In addition, we examined interclutch and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 84 publications
6
72
2
Order By: Relevance
“…Hatching success for organisms that lay eggs in a nest, such as sea turtles, is believed to be influenced by numerous biotic and abiotic factors such as predation, type of substrate, porosity, temperature, moisture content, salinity, slope of the beach, nest elevation, rainfall and tidal inundation (Mortimer, 1990;Horrocks and Scott, 1991;Ackerman, 1997;Wood and Bjorndal, 2000;Allen et al, 2001;Bilinski et al, 2001;Donlan et al, 2004;Foley et al, 2006). In many oviparous reptiles, however, environmental factors not only influence embryo survivorship (Horrocks and Scott, 1991;Resetarits, 1996), but also hatchling size (Packard and Packard, 1988), performance (Janzen, 1993), growth (Bobyn and Brooks, 1994), behaviour (Burger, 1991), and sex determination (Spotila et al, 1994). After the emergence of hatchling turtles, their survival may be strongly related to the distance at which the nest is laid from the sea and from supra-littoral vegetation behind the beach (Mrosovsky, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Hatching success for organisms that lay eggs in a nest, such as sea turtles, is believed to be influenced by numerous biotic and abiotic factors such as predation, type of substrate, porosity, temperature, moisture content, salinity, slope of the beach, nest elevation, rainfall and tidal inundation (Mortimer, 1990;Horrocks and Scott, 1991;Ackerman, 1997;Wood and Bjorndal, 2000;Allen et al, 2001;Bilinski et al, 2001;Donlan et al, 2004;Foley et al, 2006). In many oviparous reptiles, however, environmental factors not only influence embryo survivorship (Horrocks and Scott, 1991;Resetarits, 1996), but also hatchling size (Packard and Packard, 1988), performance (Janzen, 1993), growth (Bobyn and Brooks, 1994), behaviour (Burger, 1991), and sex determination (Spotila et al, 1994). After the emergence of hatchling turtles, their survival may be strongly related to the distance at which the nest is laid from the sea and from supra-littoral vegetation behind the beach (Mrosovsky, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…That different incubation temperatures can affect the hatchling phenotype via differences in size, color, growth rates, locomotor ability, and many other characteristics that may ultimately influence survival or reproductive fitness is well recorded in the reptile literature (e.g., Joanen et al 1987; Bobyn and Brooks 1994;O'Steen 1998). These effects are seen in both TSD and GSD species (Rhen and Lang,Chapter 10).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas temperature effects on certain traits may be mediated by temperature-induced variation is sex steroid levels in some species, studies in snapping turtles indicate 96 T. Rhen and J. W. Lang McKnight and Gutzke 1993Bobyn and Brooks 1994Spotila et al 1994Roosenburg 1996Roosenburg and Kelley 1996Foley 1998Demuth 2001Janzen and Morjan 2002 that temperature can have effects mediated via alternative mechanisms. In experiments described earlier, snapping turtle embryos were treated with exogenous estrogen or a potent aromatase inhibitor at the beginning of the thermosensitive period (TSP).…”
Section: Potential Mechanisms For Temperature Effects On Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…Studies of turtle 33 reproductive ecology have revealed important direct and indirect effects on fitness and 34 demography (Bobyn & Brooks, 1994;Weisrock & Janzen, 1999;Valenzuela, 2001; Spencer and 35 Thompson, 2003;Janzen et al, 2007). For example, research on the snapping turtle (Chelydra 36 serpentina) found that initial egg mass and substrate moisture were positively correlated with 37 hatchling mass, which could then affect hatchling survival (Bobyn & Brooks, 1994 (Zhang et al, 1998). Since 2014, we conducted field studies focusing on 46 habitat selection, home rage, and reproductive ecology through methods of radio telemetry, 47 spool-and-line tracking, and direct observation (Hu, 2016).…”
mentioning
confidence: 99%